Multilevel survival analysis for under-fives in Indonesia 2015 - Linta Ifada; Mieke Nurmalasari; Setia Pramana (Indonesian Pediatric Society, 2020)
Background Marking the end of the Millennium Development Goals (MDGs) era, governments continue their plans via the Sustainable Development Goals (SDGs). One of the MDGs that has continued is the reduction in under-five mortality. Even though the trend of under-five mortality in Indonesia is decreasing, more efforts are needed to reduce the under-five mortality rate. Objective To determine the individual and contextual factors of the under-five survival rate and to assess for possible characteristics that may lead to variance among regencies in Indonesia. Methods Data from 2015 Intercensal Population Survey (Survei Penduduk Antar Sensus/SUPAS 2015) in Indonesia were analyzed using multilevel survival analysis. The Intercensal Population Survey covers all regions in Indonesia up to the regency level. Data were collected by direct interviews of selected household members, with regards to demographic and household characteristics, including births and deaths of under-fives. Our sample population was limited to all under-fives who were born and died during the 2010-2015 period. The number of subjects analyzed was 219,413 after exclusion of children with incomplete data. Results Individual factors associated with under-five survival rate were maternal education, maternal age at first birth, work status, sex, previous birth interval, type of birth, place of residence, and sanitation level. The contextual factor (health care facility ratio per 1000 under-fives per regency) was not associated with under-five survival rate. The 5.27% variance can be explained by the differing characteristics among regencies. Conclusion The individual factors affecting the survival of under-fives are maternal education, maternal age at first birth, maternal work status, sex, previous birth interval, type of birth, place of residence, and sanitation level.